Lakes as a Source of Short‐Period (0.5–2 s) Microseisms. Issue 10 (28th October 2017) - Xu, Yan; Koper, Keith D.; Burlacu, Relu
Abstract: We identify and document microseisms produced by wave action in six lakes: The Great Slave Lake, Lake Ontario, Yellowstone Lake, Dianchi Lake, Fuxian Lake, and Erhai Lake. The lakes span more than 2 orders of magnitude in size (areas of 210–27, 000 km 2 ) and sample a range of climatic and tectonic regimes in Canada, the U.S., and China. Lake‐generated microseisms create spectral peaks at periods near 1 s and are often polarized as Rayleigh waves propagating away from the lake. In contrast to ocean‐generated microseisms, lake‐generated microseisms are only observed within about 25–30 km of the shoreline. This is consistent with the well‐known high attenuation of short‐period Rayleigh waves ( Rg ). It is unclear if lake‐generated microseisms are produced by a linear shoaling process, analogous to primary ocean microseisms, or a nonlinear wave‐wave interaction process, analogous to secondary ocean microseisms. If they are mainly produced by shoaling, lake‐generated microseisms might provide a spatially integrated measure of shoreline erosion. Regardless of the source mechanism, lake‐generated microseisms appear to provide a record of ice phenology for lakes that freeze in the winter. Such data could contribute to assessing the effects of climate change on high‐latitude lakes in remote areas. Finally, it is likely that lake‐generated microseisms are useful for imaging the geological structure of the shallow crust, information that is important for quantifying seismic hazard and can be difficult to obtain in urban areas where active source imaging is not feasible. Key Points: Lakes around the world commonly generate microseisms at periods of 0.5−2.0 s Lake microseisms propagate as rapidly attenuating Rg waves and are best observed at seismometers located within 25−30 km of the shoreline Lake microseisms may serve as a spatially integrative monitoring tool for freezing and ice breakup processes in lakes